TAMPILAN GULA DARAH , LAKTOSA DAN PRODUKSI SUSU SAPI PERAH LAKTASI YANG DISUPLEMENTASI BAKING SODA (NaHCO3) - Raymond C Kurniawan; C Budiarti; S M Sayuthi (MEDIAGRO, 2019)
ABSTRACT This study aims to determine the effect of the addition of baking soda as a supplement of dairy cattle feed on blood sugar, lactose, and milk production. This study used the dairy cow FH lactation of the 2nd lactation period of 5th month lactation and 6th lactation of 12 with 2-3 years old. Dairy cow FH lactation has a weight of 389.17 ± 27 kg. The treatment used was the addition of baking soda with the level of 0.8% and 1.0%. This study used a ration consisting of soybean meal, corn, brand, meat bone meal, lactoplus and forage grass uganda feed. This study used a complete randomized design consisting of 3 replication and 4 treatments. The data obtained were analyzed using variance analysis and F test at 5% level. The results showed that the addition of baking soda as supplement had no significant effect on blood sugar, lactose, and milk (P> 0,05), but it can increase milk production without supplementation (T0). The conclusion of this research is that the addition of baking soda at the level of 0.8 and 1.0% has no significant effect on blood sugar, lactose, and cow milk production. Keywords: Baking soda,blood sugar,lactose and production of diary milk